Chemical state and isotope ratio analysis of individual uranium particles by a combination of micro-Raman spectroscopy and secondary ion mass spectrometry. Issue 44 (1st November 2017) - Yomogida, T.; Esaka, F.; Magara, M.
Abstract : An analytical procedure using micro-Raman spectroscopy (MRS) and secondary ion mass spectrometry (SIMS) was developed to elucidate both the chemical states and isotope ratios of individual micron-sized uranium particles. Abstract : An analytical procedure using micro-Raman spectroscopy (MRS) and secondary ion mass spectrometry (SIMS) was developed to elucidate both the chemical states and isotope ratios of individual micron-sized uranium particles. Each uranium particle was identified by scanning electron microscopy combined with energy dispersive X-ray detection and transferred onto each specific location on a substrate by micro-manipulation. After optimization of the analytical conditions, the chemical states of each uranium particle were determined with MRS non-destructively. The substrate containing each particle was then introduced into a SIMS instrument and uranium isotope ratios of each particle were determined. The developed method is expected to be used for clarifying the origin and history of each particle in environmental samples.